Effect of ratio in ammonium nitrate on structural, microstructural, magnetic and AC conductivity properties of BaFe12O19 - Azis, Raba’ah Syahidah; Che Muda, Nor Nadhirah; Hassan, Jumiah; Shaari, Abdul Halim; Ibrahim, Idza Riati; Mustaffa, Muhammad Syazwan; Sulaiman, Sakinah; Matori, Khamirul Amin; Yap, Wing Fen (MDPI, 2018)
This paper investigates the effect of the ratio of ammonium nitrate (AN) on the structural, microstructural, magnetic, and alternating current (AC) conductivity properties of barium hexaferrite (BaFe12O19). The BaFe12O19 were prepared by using the salt melt method. The samples were synthesized using different powder-to-salt weight ratio variations (1:3, 1:4, 1:5, 1:6 and 1:7) of BaCO3 + Fe2O3 and ammonium nitrate salt. The NH4NO3 was melted on a hot plate at 170 °C. A mixture of BaCO3 and Fe2O3 were added into the NH4NO3 melt solution and stirred for several hours using a magnetic stirrer under a controlled temperature of 170 °C. The heating temperature was then increased up to 260 °C for 24 hr to produce an ash powder. The x-ray diffraction (XRD) results show the intense peak of BaFe12O19 for all the samples and the presence of a small amount of the impurity Fe2O3 in the samples, at a ratio of 1:5 and 1:6. From the Fourier transform infra-red (FTIR) spectra, the band appears at 542.71 cm−1 and 432.48 cm−1 , which corresponding to metal–oxygen bending and the vibration of the octahedral sites of BaFe12O19. The field emission scanning electron microscope (FESEM) images show that the grains of the samples appear to stick each other and agglomerate at different masses throughout the image with the grain size 5.26, 5.88, 6.14, 6.22, and 6.18 µm for the ratios 1:3, 1:4, 1:5, 1:6, and 1:7 respectively. From the vibrating sample magnetometer (VSM) analysis, the magnetic properties of the sample ratio at 1:3 show the highest value of coercivity Hc of 1317 Oe, a saturation magnetization Ms of 91 emu/g, and a remnant Mr of 44 emu/g, respectively. As the temperature rises, the AC conductivity is increases with an increase in frequency.